2007
DOI: 10.1007/s00240-007-0121-5
|View full text |Cite
|
Sign up to set email alerts
|

A nidus, crystalluria and aggregation: key ingredients for stone enlargement

Abstract: The in vitro study of calcium oxalate (CaOx) stone formation is usually based on crystallisation models but it is recognised that both healthy individuals and stone formers have crystalluria. We have established a robust in vitro stone growth model based on the principle of mixed suspension, mixed product removal system (MSMPR). Utilising this technique we studied the influence of CaOx crystallisation kinetics and the variation of calcium and oxalate concentrations on CaOx stone growth in vitro. Six stones rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Existing theories such as nucleation and supersaturation can only partly explain the formation of CaOx stones. However, both in vitro and animal studies have demonstrated that high levels of oxalate and/or calcium oxalate monohydrate (COM) is a major risk factor for the formation of stone nuclei [16][17][18]. In addition, previous studies indicated that renal tubular damage is tightly associated with the formation of kidney stones [2].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Existing theories such as nucleation and supersaturation can only partly explain the formation of CaOx stones. However, both in vitro and animal studies have demonstrated that high levels of oxalate and/or calcium oxalate monohydrate (COM) is a major risk factor for the formation of stone nuclei [16][17][18]. In addition, previous studies indicated that renal tubular damage is tightly associated with the formation of kidney stones [2].…”
Section: Discussionmentioning
confidence: 98%
“…*P < 0.05 more accurate method to measure low concentrations of molecules in a minimal specimen volume [22]. Ox, a small dicarboxylate ion, is freely filtered at the glomerulus, and its active secretion by renal proximal tubule cells contributes to the overall urinary excretion of Ox [17]. Detecting Ox amounts in urine is a simple way to evaluate the Ox metabolism [18].…”
Section: Discussionmentioning
confidence: 99%
“…The observed correlation between protein aggregate formation and CaOx crystal aggregation is likely to be critical to stone formation, because addition of preformed crystals to stone aggregates has been demonstrated repeatedly. [2224] Since most urine proteins are anionic and demonstrate similar CaOx crystal interactions, stone formation will likely be driven by highly abundant rather than trace urinary proteins, or possibly the summation of contributions from many urine proteins in the mixture.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the transformation of kidney calcifications to a clinically symptomatic stone, further crystal apposition is necessary. It probably occurs during crystalluria by crystal aggregation (AGN) [4, 5]. Crystallization processes involved in stone formation are, apart from urinary supersaturation, essentially influenced by crystallization inhibitors like citrate and urinary macromolecules (UM), the latter comprising a large group of proteins and some glycosaminoglycans [6].…”
Section: Introductionmentioning
confidence: 99%